The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11227-015-1495-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of purchase behaviors across heterogeneous social networks

Abstract: Due to the development of web services, many social network sites, as well as online shopping sites have been booming in the past decade, where it is a common phenomenon that people are likely to use multiple services at the same time. On the one hand, previous research findings indicate the data sparsity issues of online shopping accounts, which is caused by the heavy-tailed distribution of user information. On the other hand, in social network sites, the personal information and the corresponding statuses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…iv) Amazon [51]: its KG has 260K nodes of 6 types and 1.4M edges of 6 types, including 20K items. Since there are no social relationships in Amazon, we supplement it with Pokec 29 (which has 1.6M users and 30.6M friendships) according to the user profiles [52]. To capture the complementary and substitutable relationships between items, the meta-graphs are generated according to [6], and the relevance of a certain relationship regarding a meta-graph is derived according to [14].…”
Section: A Experiments Setupmentioning
confidence: 99%
“…iv) Amazon [51]: its KG has 260K nodes of 6 types and 1.4M edges of 6 types, including 20K items. Since there are no social relationships in Amazon, we supplement it with Pokec 29 (which has 1.6M users and 30.6M friendships) according to the user profiles [52]. To capture the complementary and substitutable relationships between items, the meta-graphs are generated according to [6], and the relevance of a certain relationship regarding a meta-graph is derived according to [14].…”
Section: A Experiments Setupmentioning
confidence: 99%
“…Due to the constraints of huge social network scale coupled with the sparsity of relationships between users, efficient and accurate friend recommendation on social networks presents significant challenges [23]. Aiming at the above focuses, some studies [14,22,25,28] found that it can produce effective recommendation results by transforming social networks into web graphs and then applying random walk strategy.…”
Section: Introductionmentioning
confidence: 99%